PENGARUH PERSEPSI KUALITAS DAN PERSEPSI HARGA TERHADAP PERCEIVED VALUE, CITRA PERUSAHAAN DAN MINAT KONSUMEN MEMBELI BERAS KOMERSIAL BULOG DI KOTA PEKANBARU (Jurnal Tepak Manajemen Bisnis, 2014)
Staple foods such as rice needs of Indonesiaâs populationis in creasing annually in line within creasesin population. Consumer demand forrice vary fromone customer to another. Under standing the type and qualityof rice what is needed by consumers will facilitate indetermining the marketing strategy of rice. The purpose ofthe study was to determine the effect of direct and indirect perception of quality and price perception onpurchase interest through perceived value and corporate image. The study population are consumers of rice inthe city of Pekanbaru. The number of samples are 140 people selected by purposive sampling technique. Thevariables used are perceived quality and perceived price as an independent variable, buying interest as thedependent variable and the variable perceived value and image of the company as an intervening variable. Theanalysis too lis used path analysis (path analysis). The results showed that the direct perception of productquality and price perception is positive but not significant effect on buying interest. Perceived quality andperceived price positive and significant impact directly and indirectly on buying interest through perceivedvalue but not significant through the companyâs image.While perceived value positive and significant impactonthe buying interest, while the image of the company but not significant positive effect on buying interest. The roleof mediating variables is greater than the perceived value of variables affecting the companyâs image in theperception of quality and price perceptions of the buying interest.Keyword: Perception ofQuality, PricePerception, Perceived Value, Corporate Image and Interests.